PRACTISE AND USE OF OVER-THE-COUNTER TOPICAL AND TRADITIONAL EYE MEDICINES AND THEIR EFFECTS IN FUNGAL KERATITIS CASES IN TERTIARY TEACHING HOSPITAL IN NORTHERN INDIA - Rathore, Kanchan bala; Dange, Kiran J; Gaurav A Patil (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The study goal is to evaluate the utilization and misuse of over-the-counter topical and traditional eye medications and their associated adverse effects in cases of fungal keratitis (FK) among patients. Methods: The research was conducted in the past 36 months at a tertiary teaching hospital in Northern India. All subjects provided informed consent, and the institutional ethical committee granted ethical approval. The study involved 127 cases of FK, clinically diagnosed and confirmed by a 10% KOH mount. Results: Among the baseline characteristics, 51 (40.18%) of the samples were in a 41–60-year-old age group; 78 (61.42%) were male; 116 (91.34%) were from rural areas; 114 (89.76%) had low socioeconomic status; 108 (85.4%) were illiterate; and 50 (39.37%) were farmers. According to visual acuity ratings, at the time of presentation, 57.48% of the patients had vision up to 1/60. In terms of over-the-counter medication usage, 109 (85.82%) respondents used them for the treatment of keratitis, with 64 (61.46%) using steroid drops. In the case of traditional eye medicines, 18 (14.18%) respondents used them, with 5 (27.11%) using milk and ghee. Conclusion: This study underscores the importance of addressing the misuse of over-the-counter and traditional eye medications in cases of FK and advocating for public health interventions to ensure rational and safe eye medication practices.